Risk-Informed Sustainable Development in the Rural Tropics - Tiepolo, Maurizio; Tarchiani, Vieri; Pezzoli, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Many people live in rural areas in tropical regions. Rural development is not merely a contribution to the growth of individual countries. It can be a way to reduce poverty and to increase access to water, health care, and education. Sustainable rural development can also help stop deforestation and reduce livestock, which generate most of the greenhouse gas emissions. However, efforts to achieve a sustainable rural development are often thwarted by floods, drought, heat waves, and hurricanes, which local communities are not very prepared to tackle. Agricultural practices and local planning are still not very risk-informed. These deficiencies are particularly acute in tropical regions, where many Least Developed Countries are located and where there is, however, great potential for rural development. This Special Issue contains 22 studies on best practices for risk awareness; on local risk reduction; on several cases of soil depletion, water pollution, and sustainable access to safe water; and on agronomy, earth sciences, ecology, economy, environmental engineering, geomatics, materials science, and spatial and regional planning in 12 tropical countries.